HOME SAFETY: DESAIN KEAMANAN GAS LPG DENGAN SENSOR PENDETEKSI KEBOCORAN - Cosmas Eko Suharyanto; Andi Kesuma Harahap; Alex Alfandianto (Jurnal Informatika, 2020)
Liquefied Petroleum Gas (LPG) is a diversion program undertaken by the government and become a modern household items today. The risk of the use of LPG is leakage of gas tube or gas hose. Gas leakage can couse explosion or fire resulting in many deaths and injuries. Governments have to disseminate the home safety of LPG and train how to mitigate household accident. This work aimed to minimize the possibility of fire and created a tool that is able to detect leakage of LPG  using gas sensor and Arduino Uno. We create a mechanical design diagram as a model that illustrates the relationships between sub-systems. When the sensor detects the LPG gas, the system activates the relay and indicator lights. In addition, this tool can send SMS in case of leakage of gas, so that action can be done quickly to stop the gas flow.